The archaeology and history of the Church of the Redeemer and the Muristan in Jerusalem : a collection of essays from a workshop on the Church of the Redeemer and its vicinity held on 8th/9th September 2014 in Jerusalem - Vieweger, Dieter, 1958-; Gibson, Shimon, (Archaeopress, 2016)
This monograph contains fifteen chapters written by leading scholars from around the world dealing with the archaeological and historical aspects of the Muristan from the Iron Age through to Ottoman times.